RETRACTED: Experimental and theoretical investigations of Erbium complex: DNA/BSA interaction, anticancer and antibacterial studies - Thanoon, Raid D.; Ibadi, Emam Atiyah; Ahmad, Irfan; Alamir, Hassan Thoulfikar A.; Alwan, Marim; Hashim, Furqan S.; Khaled, Donia Waleed; Alkhafaji, Adnan Taan; Asiri, Mohammed; Alsaalamy, Ali (Frontiers in Chemistry, 2023)
To assess the biological potential of an Er complex that contains a 2,2'-bipyridine ligand, various techniques such as multispectral and molecular modeling procedures were utilized to examine its DNA-binding ability, BSA binding affinity, antimicrobial effects, and anticancer properties. By analyzing fluorescent information and employing the vant' Hoff equation, important parameters such as the innate docking coefficient (Kb), Stern-Volmer coefficient (KSV), and thermodynamic properties including modifications in liberated energy (ΔGº), enthalpy (∆Hº), and entropy (∆Sº) were determined. The trial findings suggest that the compound can bind to DNA, primarily through groove binding. Additionally, the engagement between the Er compound and the protein BSA was examined using emission spectroscopy technique, revealing a powerful binding affinity between the compound and BSA. The Er complex binds to BSA primarily via hydrogen links and van der Waals forces, as indicated by the adverse values of ΔHº and ∆Sº. Through a static quenching process, the complex significantly reduces the intrinsic fluorescence of BSA.Molecular binding calculations and rivalrous binding trials confirm that this compound dock to hydrophobic remains found in site III of BSA. Additionally, the Er complex demonstrates promising results in terms of its anticancer and antimicrobial activities based on screening tests.